Hubungan Kadar Kreatinin dan Ureum dengan Derajat Anemia pada Pasien Penyakit Ginjal Kronik di RSUD Sanjiwani Gianyar - Ni Wayan Ayu Maha Dewi; Luh Gede Sri Yenny; Putu Nita Cahyawati (Fakultas Ilmu Kedokteran dan Ilmu Kesehatan, Universitas Warmadewa, 2023)
Chronic kidney disease (CKD) is still a world health problem, that showed by an increasing prevalence every year. CKD causes kidney damage which is assessed by increased levels of creatinine and urea. One of the health problems that can occur in CKD patients is anemia. The purpose of this study is to determine the relationship between creatinine and urea levels with the degree of anemia, by using analytical research methods with a cross-sectional study design. The data collection method used secondary data from medical records. The research samples are 80 CKD patients at the Sanjiwani Hospital, Gianyar who qualified the inclusion and exclusion criteria with consecutive sampling techniques. Data were analyzed by univariate and bivariate analysis. The results showed that patients with CKD were dominated by men (60%), with an age range of 50-59 years (55%), and dominated by CKD stage V (78.8%). The highest average creatinine and urea levels were found in CKD stage V, which was 11.41 mg/dL and 143.72 mg/dL, while the lowest average of hemoglobin level was found in CKD grade V (9.07 g/dL). The results of the analysis of the One way annova test showed that the value of p=0.003 for creatinine and p=0.001 for urea (p<0.05). Based on these results, it can be concluded that there is a significant relationship between creatinine levels with moderate anemic patients (p=0.003) and severe anemic patients (p=0.003) using the Bonferroni post hoc test, and also there is a significant relationship between urea levels with moderate anemic patients (p=0.022) and severe anemic patients (p=0.022) using the Games-Howell post hoc test.